Analysis Of Translation Techniques On Public Signs In Jabodebek Light Rail Transit (LRT) - Estetika, Millenia; Gusthini, Misyi (Jurnal Ilmu Sosial dan Humaniora, 2024)
Public signs are signs in public facilities that provide information, directions, warnings, or notifications that aim to help people get the right and accurate information. In this research, the researcher researched the public signs on Jabodebek LRT with two destination routes, namely the Bogor Line (Dukuh Atas Station–Harjamukti Station) and the Bekasi Line (Dukuh Atas Station–Jatimulya Station). The Jabodebek LRT public signs are translated into English from Indonesian. Analyzing the translation techniques used to convert the Indonesian (source text) into the English (target language) is the aim of this research. By referring to the concept of translation techniques submitted by Molina and Albir (2002), out of 18 translation techniques, only 6 were identified to be used in 13 public signs. The researcher researched the techniques of translation used to translate the Indonesian public signs, which involve adaptation, substitution, literal translation, established equivalent, modulation, and description techniques. According to the researcher's analysis of the 13 public signs in the Jabodebek LRT, the translation's final product has much greater readability, accuracy, and acceptability when the appropriate translation technique is used that is specific to the specific setting being studied. In addition, the source text and the target text are textually equivalent in that both texts are similar in meaning, significance, and information conveyed, although there may be differences in sentence structure, word choice, or language style.